2009
DOI: 10.1124/jpet.109.157230
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of α2-Adrenoceptor Functions by Heterotrimeric Gαi Protein Isoforms

Abstract: Subtype diversity of heterotrimeric G proteins and G proteincoupled receptors enables a wide spectrum of signal transduction. However, the significance of isoforms within receptor or G protein subfamilies has not been fully elucidated. In the present study, we have tested whether ␣ 2 -adrenoceptors require specific G␣ isoforms for their function in vivo. In particular, we analyzed the role of the highly homologous G␣ i isoforms, G␣ i1 , G␣ i2 , and G␣ i3 , in typical ␣ 2 -adrenoceptor-controlled functions. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…In this study, we used mouse strains deficient for Ga i2 or Ga i3 , which have been previously characterized (16,22,24,28). It should be pointed out that Ga i2 -deficient animals were strictly kept under pathogen-free conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used mouse strains deficient for Ga i2 or Ga i3 , which have been previously characterized (16,22,24,28). It should be pointed out that Ga i2 -deficient animals were strictly kept under pathogen-free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These Ga i knockout (KO) mouse strains were backcrossed to C57BL/6J mice for more than 11 generations and kept in inhalator ventilation cages (IVC) (Ga i2 2/2 ) or under specific pathogen-free (SPF; Ga i3 2/2 ) conditions (24). No obvious signs of intestinal inflammation were visible during the course of the study, and IVC-kept Ga i2 -deficient mice show similar survival as wild-type (WT) mice (see Supplemental Fig.…”
Section: Micementioning
confidence: 99%
“…These Ga i knockout (KO) mouse strains were backcrossed to C57BL/6J (B6) mice for .11 generations and were strictly kept under IVC conditions. Under these conditions, no signs of intestinal inflammation were visible in Ga i2 -deficient mice during the course of the study (15). C5aR-deficient mice backcrossed to C57BL/6J mice for six generations were provided by C. Gerard (Boston, MA) (25).…”
Section: Micementioning
confidence: 99%
“…Many biological functions of leukocytes, including macrophage phagocytosis and migration, involve Ga i -mediated signaling (11,12). Previous studies in mice lacking Ga i2 or Ga i3 suggested key roles of these two G i isoforms in distinct cellular responses (13)(14)(15)(16). For instance, Ga i3 deficiency leads to an impaired response of insulin-regulated autophagy in liver cells (16,17), whereas Ga i2 2/2 mice show defects in the migration of T and B cells to lymph nodes (18,19) and of eosinophils to sites of allergic tissue injury (20).…”
mentioning
confidence: 99%
“…Given that both a 2A -adrenergic and 5-HT 1A receptors are coupled to inhibitory G proteins, 40,41 we used western blotting and qRT-PCR to assess the expression levels of Gi/o-like proteins and mRNAs in the LC, the DRN and the PFC after a repeated MDMA exposure. We found that mice repeatedly injected with MDMA exhibited significant less Gai 1 and Gai 2 immunoreactivity within the LC (t ¼ 3.176, Po0.05 and t ¼ 3.744, Po0.05 for Gai 1 and Gai 2 , respectively) (Figures 5e and f) and Gai 3 immunoreactivity within the DRN (t ¼ 3.042, Po0.05) than controls (Figures 5g and h).…”
Section: Acutementioning
confidence: 99%